2004
DOI: 10.1123/jsr.13.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Six Weeks of Strength and Proprioception Training Does Not Affect Muscle Fatigue and Static Balance in Functional Ankle Instability

Abstract: Context:The combined effects of strength and proprioception training, especially in individuals with ankle instability, have not been studied extensively.Objective:To examine the influence of 6 weeks of strength and proprioception training on measures of muscle fatigue and static balance in those with unilateral functional ankle instability (FAI).Design:Pretest–posttest, randomized groups.Setting:A climate-controlled sports-medicine research laboratory.Subjects:38 subjects with self-reported unilateral FAI.Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…18,24,25 Conflicting findings exist in the current literature 14,23 ; thus, the relationship between strength training and other factors, such as balance, proprioception, or functional performance, requires further investigation. Most authors 18,20,21,23,25 who have investigated the effect of strength training in people with CAI have used resistivetubing exercises 3 times/wk for 4 weeks 20 to 6 weeks. 18,21,23,25 Other rehabilitation protocols have involved manual resistance at the ankle 22 and isokinetic strength training.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…18,24,25 Conflicting findings exist in the current literature 14,23 ; thus, the relationship between strength training and other factors, such as balance, proprioception, or functional performance, requires further investigation. Most authors 18,20,21,23,25 who have investigated the effect of strength training in people with CAI have used resistivetubing exercises 3 times/wk for 4 weeks 20 to 6 weeks. 18,21,23,25 Other rehabilitation protocols have involved manual resistance at the ankle 22 and isokinetic strength training.…”
mentioning
confidence: 66%
“…Most authors 18,20,21,23,25 who have investigated the effect of strength training in people with CAI have used resistivetubing exercises 3 times/wk for 4 weeks 20 to 6 weeks. 18,21,23,25 Other rehabilitation protocols have involved manual resistance at the ankle 22 and isokinetic strength training. 24 Some researchers 18,21,[23][24][25] focused on strengthtraining protocols alone, whereas others 19,20,22,27,28 have used multicomponent protocols that included balance exercises.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6À10 Whereas some of these therapeutic techniques yielded positive outcomes for balance control and anklejoint stability, 11,12 others have been less successful. 13,14 One potential explanation for these conflicting findings is limited understanding about how individuals with CAI react to these disturbances. Thus, measuring their postural control during actual perturbation tasks might yield useful information because such tasks and conditions are often accompanied by a sensation of ankle instability.…”
mentioning
confidence: 98%
“…12 Although research suggests an improvement in symptoms of ankle instability with the intervention of wobble board training, 13 others contradict this claim indicating no significant improvement in balance or muscle function. 14,15 A meta-analysis by Van der Wees et al 16 indicated that rehabilitation programs based on wobble board proprioceptive exercises could be considered clinically effective in ankle rehabilitation. This assumption, however, has been challenged on the basis that wobble board training alone does not actually target ankle proprioception deficits.…”
Section: Introductionmentioning
confidence: 99%